The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13071-019-3494-8
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex PCR assay for the identification of five species of the Anopheles barbirostris complex in Thailand

Abstract: Background The Barbirostris Complex comprises six formally described species that cannot be differentiated based on morphology alone. Out of these six species, two have been reported as putative malaria vectors, An. campestris and An. wejchoochotei . Five species are present in Thailand, An. barbirostris , An. campestris , An. dissidens , An. saeungae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…barbirostris . The ITS2 sequence was compared to voucher sequences and primer sites used in Brosseau et al [ 17 ], as the highest homology was to these sequences. Although most similar to An.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…barbirostris . The ITS2 sequence was compared to voucher sequences and primer sites used in Brosseau et al [ 17 ], as the highest homology was to these sequences. Although most similar to An.…”
Section: Resultsmentioning
confidence: 99%
“…Consensus sequences of each sequence group were compared (BLASTn) to the NCBI nr and BOLD databases to identify species. Sequences mapping to the Funestus Group, Hyrcanus Group, Barbirostris Complex, Sundaicus Complex and Maculatus Group were compared to voucher sequences and primers used in diagnostic PCR [ 17 , 33 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…barbirostris s.l. [59] could bind to the ITSII sequences generated in our study, and they amplified a 404-bp fragment (Additional File…”
Section: The Itsii Region and Coi Gene [See Additional Files 3 And 4 Fomentioning
confidence: 97%
“…barbirostris s. l., including those generated in this study, were also aligned without trimming using the parameters stated above. Primer binding sites for the multiplex PCR assay developed by Brosseau et al [58] to identify the members of the Barbirostris Complex were then identified from the alignment. Amplicon size(s) resulting from the multiplex PCR assay was also determined for the ITSII sequences generated from this study.…”
Section: Analysis Of Primer Binding Sites In the Itsii Sequence Of Anmentioning
confidence: 99%